1992
DOI: 10.1007/bf00120650
|View full text |Cite
|
Sign up to set email alerts
|

The use of electrophoretic markers in seed orchard research

Abstract: Gene flow is a critical determinant of population genetic structure, playing an important role in forest tree improvement, conservation genetics, and the potential for the escape of engineered genes. A review of gene flow among plant populations yields the following generalization: although gene flow varies substantially among species, populations, seasons, and even individual plants, at physical isolation distances of hundreds to thousands of meters, gene flow levels are frequently sufficient to counteract ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 35 publications
0
7
1
Order By: Relevance
“…The first checkpoint would be the correctness of the ramets of clones in breeding arboreta on which crosses are going to be made for progeny trials from which new selections will eventually be made. On average about 10 % of ramets were found to have the incorrect genotype in species such as Douglas-fir, Scots pine and loblolly pine (ADAMS, 1983;HARJU and MUONA, 1989;WHEELER and JECH, 1992). The average figure in this study of 2.6 % is therefore low, especially when it is considered that overall PI values with the microsatellites are so low that all errors should be detected unequivocally, unlike perhaps with isozyme markers used in earlier studies.…”
Section: Discussioncontrasting
confidence: 55%
“…The first checkpoint would be the correctness of the ramets of clones in breeding arboreta on which crosses are going to be made for progeny trials from which new selections will eventually be made. On average about 10 % of ramets were found to have the incorrect genotype in species such as Douglas-fir, Scots pine and loblolly pine (ADAMS, 1983;HARJU and MUONA, 1989;WHEELER and JECH, 1992). The average figure in this study of 2.6 % is therefore low, especially when it is considered that overall PI values with the microsatellites are so low that all errors should be detected unequivocally, unlike perhaps with isozyme markers used in earlier studies.…”
Section: Discussioncontrasting
confidence: 55%
“…Several studies using genetic markers have demonstrated that a large proportion of a young orchard's seed crop is fertilized by unselected contaminant sources (Stoehr et al 1998;Harju and Nikkanen 1996;Paule et al 1993;Wheeler and Jech 1992;Yazdani and Lindgren 1991). It is also the case in mature seed orchards (reviewed by Adams et al 1997).…”
Section: Estimation Of Pollen Contamination and Loss Of Genetic Gainmentioning
confidence: 99%
“…Understanding levels of pollen gene flow is important for evolutionary and conservation biologists (Neigel 1997; Sork et al . 1999), but also for the practical management of gene pools in commercial agriculture crops and forest populations (Wheeler & Jech 1992; Orson & Oldfield 1999; Adams & Burczyk 2000), especially as more transgenic species are introduced (Rogers & Parkes 1995). Direct estimation methods using genetic markers and paternity exclusion are considered reliable tools for assessing contemporary pollen gene flow (Bossart & Prowell 1998; Sork et al .…”
Section: Introductionmentioning
confidence: 99%